2004
DOI: 10.1161/01.cir.0000124488.06377.77
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Risk of Secondary Cardiovascular Events in Women

Abstract: Background-In apparently healthy people, the relation between blood pressure and risk of subsequent cardiovascular disease (CVD) is linear. In persons with CVD, the relation is uncertain. Methods and Results-We conducted a prospective study of 5218 older women with CVD who reported their blood pressure at baseline in the Women's Antioxidant Cardiovascular Study (WACS), an ongoing double-blind, placebocontrolled secondary prevention trial of the benefits and risks of antioxidant vitamins, folic acid, vitamin B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 30 publications
(22 reference statements)
1
14
0
1
Order By: Relevance
“…Moreover, results from this study also show that systolic ABPM was a significant predictor of cardiovascular risk over and above conventional systolic blood pressure [35]. In women with cardiovascular disease, systolic blood pressure was the blood pressure measure most strongly related to the risk of secondary cardiovascular events [36] (Fig. 6).…”
Section: Isolated Systolic Hypertensionsupporting
confidence: 54%
“…Moreover, results from this study also show that systolic ABPM was a significant predictor of cardiovascular risk over and above conventional systolic blood pressure [35]. In women with cardiovascular disease, systolic blood pressure was the blood pressure measure most strongly related to the risk of secondary cardiovascular events [36] (Fig. 6).…”
Section: Isolated Systolic Hypertensionsupporting
confidence: 54%
“…Our data further showed that individuals who viewed their own behavior as ambivalent exhibited greater DBP over the course of the day than individuals whose own behavior was perceived as supportive. SBP has been recognized in both men and women as a strong linear predictor of cardiovascular disease [59, 60] with increased risk already evident with high-normal SBP (120–139) [61]. A sustained 12-mmHg decrease in SBP for 10 years will prevent one death for every 11 hypertensive patients treated [62].…”
Section: Discussionmentioning
confidence: 99%
“…Although traditionally in clinical settings hsCRP levels greater than 10 mg/L have been associated with acute illness, infections or autoimmune disorders not CVD risk, data from the Women’s Health study showed that hsCRP values remain predictive for cardiovascular events for the entire range of values 22, 23 . In fact, women in the Women’s Health Study with hsCRP values >10 mg/L were considered to be a “very high risk” group and those with hsCRP values ≥20 mg/L were observed to be at exceptionally elevated risk for vascular disease.…”
Section: Introductionmentioning
confidence: 99%